Bronchiectasis in low- and middle-income countries: the importance of the wider view. Issue 1 (5th January 2023) - Brown, Jeremy S.; Hurst, John R.
Until the early 2000s, PubMed data showed there were fewer than 200 papers published on bronchiectasis per year. Since then, publications on bronchiectasis have increased rapidly to a peak of 834 publications in 2021 (for context, just over 10% of the total for COPD or asthma). The quality of the published data has also improved substantially, and now includes large epidemiology datasets, clinical insights from disease registry studies, and multiple controlled trials. This body of work has shown that bronchiectasis, far from being a disease from the history books, is increasing in incidence in high income countries (HICs), at least in part due to the greater accessibility of computed tomography (CT) lung scanning, and has defined severity scoring systems, causative aetiologies, novel disease phenotypes, and effective therapies [1–6]. However, a major limitation has been the very limited data published on bronchiectasis from countries other than Europe, the USA and Australasia. Bronchiectasis is the end consequence of multiple different aetiologies, many of which (such as previous severe lung infections and tuberculosis (TB)) have a higher prevalence in low and middle income countries (LMICs). As a result, the published data on bronchiectasis probably does not accurately reflect the global burden of bronchiectasis, nor provide the clinical insights needed to improve management in LMICs. The clinical characteristics and predictors for poor outcome for patients with bronchiectasis has important differences in India compared with high-income countries, and this will impact on the optimum management of these patients. https://bit.ly/3UfRzjw